Approccio strategico alla produzione - Christian, Simoni (Studi e saggi, 2002)
The strategic value of operations is the leitmotif that runs through the entire book. Based on this, in the first chapter the author proposes a reading of production strategy that goes beyond a content and category approach to include aspects of positioning (strategic groups of manufacturers), goals, perspectives, strategic ploys, patterns and plans as well as resources and skills. Chapter two then addresses world class manufacturing, conceived as a system of basic principles, guidelines and general criteria for the design and management of the production system that appears to characterise outstanding enterprises. Onto this three fundamental approaches of streamlined production can be effectively grafted: Just-In-Time, Total Quality Management and employee empowerment. Finally chapter three represents an initial attempt at verification of the formulated theories.